The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-90758-7
|View full text |Cite
|
Sign up to set email alerts
|

Isotonic quadriceps endurance is better associated with daily physical activity than quadriceps strength and power in COPD: an international multicentre cross-sectional trial

Abstract: Knowledge about modifiable determinants of daily physical activity (PA) in patients with chronic obstructive pulmonary disease (COPD) is crucial to design effective PA interventions. The present study aimed to determine the contribution of quadriceps strength, power and endurance to daily PA in COPD. Additionally, for quadriceps endurance, we also aimed to determine to what extent the association varies according to the mode of movement (isotonic, isometric, or isokinetic). Using a multicentre cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…A study by Frykholm et al found that increased isotonic quadriceps endurance is associated with reduced sedentary time. 44 …”
Section: Resultsmentioning
confidence: 99%
“…A study by Frykholm et al found that increased isotonic quadriceps endurance is associated with reduced sedentary time. 44 …”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests that people with COPD avoid participation in PA owing to the perception of breathlessness, leading to a vicious circle of muscle deconditioning, further compromising their capacity to engage in PA [3,[9][10][11][12]. However, improving the level of PA in people with COPD is complex, as PA behavior itself is complex and multifaceted, including, for example, personal, physiological, and psychological elements as well as social and environmental factors [1,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, despite the wide range of available methods, their effect on PA in patients with COPD is limited, which might be attributed to an incomplete understanding of the determinants of PA behavior in the COPD population [12,15]. Although a variety of determinants of PA have been identified, including, but not limited to, exercise capacity, previous exacerbations, dyspnea, quadriceps dysfunction, and hyperinflation [11,[15][16][17], the available information does not clearly answer the determinants of PA in patients with COPD. This is mostly because the available research has been cross-sectional [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, muscle power showed a stronger association with functional performance than muscle strength in healthy older adults and patients with neurological diseases [7][8][9]. Similarly, cross-sectional studies have found associations between muscle power and functional performance [10,11] or physical activity [12,13] in individuals with COPD. However, to the best of our knowledge, only one study has reported reduced lower extremity peak power in older adults with COPD compared with healthy subjects so far [14].…”
Section: Introductionmentioning
confidence: 99%